Analisis Efisiensi Keluaran Daya Solar Sel Berdasarkan Sudut Kemiringan - Kurniati, Sri; S, Sudirman (Universitas Nusa Cendana, 2013)
This study aims to analyze the efficiency of solar cells based on elevation angle. In this system installed panel of 100 Wp solar cells, electrical energy for charging the battery 140 Ah, and a inverter 1300 Watt to turn on the fluorescent lights and the supply of energy resources. The method used is to experiment with the adjust the angle elevation of solar panels in the charging battery cells. The results showed the maximum capacity of the electric power that is able to operate in the application of 350 Watt with elevation position 25O.